PostgreSQL server programming : extend PostgreSQL using PostgreSQL server programming to create, test, debug, and optimize a range of user-defined functions in your favorite programming language /: extend PostgreSQL using PostgreSQL server programming to create, test, debug, and optimize a range of user-defined functions in your favorite programming language. (2015) - Dar, Usama; Krosing, Hannu; Mlodgenski, Jim; Roybal, Kirk
No abstract available